Analisis Pengaruh Penerapan Sistem Integrasi Tanaman Kakao dan Ternak Kambing Terhadap Pendapatan Petani di Kecamatan Tapango Polewali Mandar - Syafruddin, Syafruddin (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Tapango District has sufficient cocoa potential to become a source of community income. Management and income generation can be achieved by integrating cocoa plantations with goats. Mathematically the integration of cocoa and goats can affect farmers' income. What's more, the price of cocoa is currently increasing. Likewise with the sale of goats as additional income for farmers. The integration of cocoa plants with goats has been a tradition in Tapango District for a long time and at the same time as saving for farmers to cover unexpected costs. These opportunities and challenges go hand in hand because of the factors that affect the integration system of cocoa plants and goats. Therefore, this study aims to examine the relationship between the two and other factors that influence the income of farmers in Tapango District. This study is a quantitative descriptive study, the data obtained in this study was carried out by observation techniques, namely collecting information by making direct observations of the research location and interview techniques, namely by collecting information by asking and answering questions through respondents totaling 30 people who owned cocoa land and integrate with goats. To find out the relationship between several independent variables and the dependent variable, Multiple Linear Regression Analysis was used. Factors of age, education, land area, number of livestock, land status and other occupations have a significant effect on increasing farmers' income in Tapango District. The results of the study along with the test equipment and Multiple Linear Regression Analysis showed that these factors had a significant and even very real effect on increasing farmers' income